HIV/AIDS conspiracy beliefs and intention to adopt preexposure prophylaxis among black men who have sex with men in Los Angeles. (March 2018) - Brooks, Ronald A; Allen, Vincent C; Regan, Rotrease; Mutchler, Matt G; Cervantes-Tadeo, Ramon; Lee, Sung-Jae
In the United States, black men who have sex with men (MSM) are the group most affected by the HIV/AIDS epidemic. Pre-exposure prophylaxis (PrEP) is an important new HIV prevention strategy that may help reduce new HIV infections among black MSM. This analysis examined the association between HIV/AIDS conspiracy beliefs and intentions to adopt PrEP among 224 black MSM. The likelihood of adopting PrEP was assessed and more than half (60%) of the study population indicated a high intention to adopt PrEP. HIV/AIDS genocidal and treatment-related conspiracies were assessed using scales previously validated with black MSM. Almost two-thirds (63%) endorsed at least one of eight HIV/AIDS conspiracy beliefs presented. In multivariable analyses, black MSM who agreed with the genocidal or treatment-related conspiracy beliefs scales had a lower intention to adopt PrEP (Adjusted Odds Ratio [AOR] = 0.73, 95% CI = 0.54, 0.99 and AOR = 0.36, 95% CI = 0.23, 0.55, respectively). Our findings indicate that preexisting HIV/AIDS conspiracy beliefs may deter some black MSM from adopting PrEP. We suggest strategies PrEP implementers may want to employ to address the influence that HIV/AIDS conspiracy beliefs may have on the adoption of PrEP among black MSM, a population disproportionately affected by HIV/AIDS.